Coordination in archery: difference between beginner and the world-class athlete - Tejo Machado, N.; Carvalheiro Reiser, F.; de Sousa Palha Santos, E.; Valtner, T. T.; Ervilha, U.; Aoki, M. S.; Magalhães, F. H.; Mochizuki, L. (Archives of Sports Science, 2017)
Objective: This study aims to analyze muscle activity during the archers shoot an arrow with the bow in an Olympic competition simulation (72 arrows in 12 blocks of 6 shots). Methods: Data were collected from an Olympic simulation performed by an experienced archer and a beginner archer. The muscle activity data were collected by surface electrodes and the accelerometer determined the beginning of the movement. Statistical analysis used ANOVA One-way and Tukey's post-test. Results: The beginner archer does not have a pattern of muscle activation. Therefore, the experienced Archer showed differences in the lumbar stabilization in the first blocks decreased over the blocks. The serratus m uscle Previous had significant difference in side pulling the rope when compared to the side that stabilizes the bow. Conclusion: The beginner archer can acquire with time, a pattern of activation, making it to select the best shot technique.